Detection of permafrost in shallow bedrock areas with the opposing coils transient electromagnetic method - Yang, Guiqian; Xie, Changwei; Wu, Tonghua; Wu, Xiaodong; Zhang, Yuxin; Wang, Wu; Liu, Guangyue (Frontiers in Environmental Science, 2022)
Transient electromagnetic method (TEM) is a method of detecting underground geological body by using the principle of electromagnetic induction, which has been widely used in permafrost exploration. In the practical application of TEM to investigate permafrost, it is found that in some areas where the bedrock is buried shallowly, the electrical resistivity near the surface cannot be obtained, and both frozen soil and underground bedrock respond to high electrical resistivity, so it is difficult to get the distribution characteristics of the permafrost thickness. Based on this background, by analyzing the measured data, it is considered that the reason for this situation is that the noise superposition generated by the receiving coil under the action of a primary field forms a shallow detection blind area. This study tries to use the equivalent anti flux opposing-coils to eliminate the blind area, and measured it in the permafrost area of Mahan mountain in Lanzhou. The results show that the opposing-coils transient electromagnetic method (OCTEM) can clearly detect the low resistance anomaly near the boundary and permafrost base in Mahan mountain, solve the problem of shallow detection blind area of conventional TEM, effectively eliminate the interference caused by primary field, and greatly improve the horizontal and vertical resolution.